The Queen : the forgotten life behind an American myth - Levin, Josh, 1980- (Back Bay Books, 2019)
"In the fall of 1974, the Chicago Tribune found a woman its readers were sure to hate. Linda Taylor had reported a phony burglary, concocting a lie about stolen furs and jewelry. The detective who checked it out soon discovered she was a scammer, a welfare cheat who drove a Cadillac to collect ill-gotten government checks. Taylor, it turned out, was also a kidnapper, and possibly a murderer. But nobody--not the journalists who touted her story, not the police, and not Ronald Reagan, who railed against Taylor during the 1976 presidential campaign--seemed to care about anything but her welfare thievery. Levin's mesmerizing book, the product of six years of reporting and research, is an empathetic work of true crime, an account of how Taylor destroyed both strangers and those close to her ... Growing up in the Jim Crow South, Taylor was made an outcast because of the color of her skin. As she rose to infamy, the press and politicians manipulated her image to demonize poor black women. This is the dazzling story of what was done to Linda Taylor, what she did to others, and what was done in her name."--Jacket